Influenza vaccination for heart failure patients: a cost-effectiveness analysis from the perspective of Chinese healthcare system - Minting Zhao; Minting Zhao; Fuqiang Liu; Lan Wang; Dan Chen; Dan Chen (Frontiers Media S.A., 2024)
PurposeInfluenza infection induces cardiovascular events in heart failure (HF) patients, with potential risk reduction through vaccination. This study aims to evaluate the cost-effectiveness of influenza vaccination for HF patients in China.MethodsWe developed a Markov model with a 3-month cycle to simulate the cost-effectiveness of administering the influenza vaccine to patients with HF over a 3-year period. Patients in the model received either the influenza vaccine or a placebo, in addition to standard HF treatment. Cost data, sourced from the China Healthcare Statistic Yearbook and other public records, and effectiveness data from the IVVE (Influenza Vaccine to Prevent Adverse Vascular Events in HF) trial, were incorporated. Specifically, the cost of the influenza vaccine was 75 Chinese Yuan (CNY) (11 USD), the cost of hospitalization for heart failure (HHF) was 9,326 CNY (1,386 USD), and the cost of treatment for pneumonia was 5,984 CNY (889 USD). The study's primary outcome, the incremental cost-effectiveness ratio (ICER), quantifies the incremental cost (CNY and USD) per incremental quality-adjusted life year (QALY). Additional outcomes included total cost, total effectiveness, incremental cost, and incremental effectiveness. We conducted one-way and probabilistic sensitivity analyses (PSA) to assess certainty and uncertainty, respectively. Scenario analysis, considering various situations, was performed to evaluate the robustness of the results.ResultsIn the base case analysis, influenza vaccine, compared to placebo, among Chinese HF patients, resulted in a cost increase from 21,004 CNY (3,121 USD) to 21,062 CNY (3,130 USD) and in QALYs from 1.89 to 1.92 (2.55 life years vs. 2.57 life years) per patient. The resulting ICER was 2,331 CNY (346 USD) per QALY [2,080 CNY (309 USD) per life year], falling below the willingness-to-pay threshold based on per capita GDP. One-way sensitivity analysis revealed that disparities in HHF and cardiovascular death rates between groups had the most significant impact on the ICER, while the cost of vaccines had a marginal impact. PSA and scenario analysis collectively affirmed the robustness of our findings.ConclusionThis study suggests that adding the influenza vaccine to standard treatment regimens for Chinese patients with HF may represent a highly cost-effective option. Further real-world data studies are essential to validate these findings.